Real-world use of once-weekly semaglutide in patients with type 2 diabetes at an outpatient clinic in Spain - Garcia de Lucas, Maria Dolores; Miramontes-González, Jose Pablo; Avilés-Bueno, Beatriz; Jiménez-Millán, Ana Isabel; Rivas-Ruiz, Francisco; Pérez-Belmonte, Luis M. (Frontiers in Endocrinology, 2022)
Objectives: To investigate the use of once-weekly semaglutide in a real population of patients with type 2 diabetes mellitus (T2DM) in three Spanish hospitals. Method: An observational, retrospective and multicenter clinical study was designed that included 166 patients with T2DM, distinguishing between a group naïve to GLP-1RA (n=72) and another switching from another GLP-1RA (n=94), all managed in the outpatient clinical setting. The primary endpoint was the change in HbA1c from baseline to the end of the study. The secondary endpoints included changes in body weight and the proportion of patients achieving HbA1c <7.0% and body weight loss >5%. Results: After 24 months of follow-up, the reductions in HbA1c were -0.91±0.7% (p<0.001) in the total cohort, -1.13±1.38% (p<0.019) for GLP-1RA-naïve patients, and -0.74±0.9% (p<0.023) for GLP-1RA-experienced patients. Body weight reductions were -12.42±9.1% in GLP-1RA-naïve patients vs. -7.65±9.7% in GLP-1RA-experienced patients (p<0.001). In the total cohort, 77.1% reached the objective of an HbA1c level <7%, and 12.7% reached between 7.1% and 7.5%. Additionally, 66.9% achieved a weight reduction ≥5%. Of all patients, 90% received 1 mg of semaglutide once a week. The reported adverse events were consistent with the known safety profile of semaglutide. Conclusions: In routine clinical practice in Spain, the use of semaglutide once a week was associated with statistically significant and clinically relevant improvements in HbA1c and body weight in a wide range of adults with T2DM, without notable adverse effects, which supports real-world use.